2019
DOI: 10.1177/0361198119850150
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica Coatings to Improve the Tensile Bond Strength of Cementitious Grouts

Abstract: The use of prefabricated bridge elements (PBEs) is becoming more common as bridge owners strive to construct robust bridges with minimal impacts on the traveling public. Concrete PBEs offer advantages with regards to quality and construction safety; however, to perform adequately, the installed structural system must include strong, durable connections between the components. Typically, field-cast cementitious grouts are used to connect the PBE. This type of material has at times shown serviceability problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They found that polyurethane coating has the highest strength and the lowest corrosion rate, while concrete with polypropylene fibers has the highest compressive strength. De la Varga [ 14 ] developed nanosilica coatings to improve the pull-off strength of cementitious materials. Morshed et al [ 15 ] showed that the addition of nanosilica and multi-wall carbon nanotubes to epoxy resin has a positive effect on the bonding between fiber-reinforced polymer composites and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…They found that polyurethane coating has the highest strength and the lowest corrosion rate, while concrete with polypropylene fibers has the highest compressive strength. De la Varga [ 14 ] developed nanosilica coatings to improve the pull-off strength of cementitious materials. Morshed et al [ 15 ] showed that the addition of nanosilica and multi-wall carbon nanotubes to epoxy resin has a positive effect on the bonding between fiber-reinforced polymer composites and concrete.…”
Section: Introductionmentioning
confidence: 99%